A Linguistic Landscape Study of Culinary Store Names on Jalan Soekarno-Hatta, Malang - Putri Sekarsari; Ririn Pratiwi Suharto (Universitas Nahdlatul Ulama Blitar, 2026)
Malang is known for its diverse culinary attractions, particularly along Jalan Soekarno-Hatta, a popular culinary area. The linguistic landscape (LL) displayed in public spaces reflects the sociolinguistic characteristics of a region and can be observed through culinary store names. This study aims to identify the monolingual and bilingual patterns used in culinary store naming on Jalan Soekarno-Hatta and to analyze their informational and symbolic functions. This research employed a descriptive qualitative method. Data were collected from permanent signage along Jalan Soekarno-Hatta. Of the 181 stores identified, 80 were culinary businesses. The findings reveal 70 monolingual store names categorized into six patterns: P+BN, BN, TCS+P, TCS+P+BN, TCS+BN, and P. In addition, 10 bilingual store names were classified into three patterns: TCS+BN, P+BN, and TCS+P. The study shows that the informational function of the linguistic landscape is to communicate products and store locations, while the symbolic function reflects business ownership and the regional identity of the cuisine offered. These findings demonstrate how culinary store names contribute to representing cultural and linguistic identities in urban public spaces.